Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Éditions du Seuil, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Section: 1 vol. (249 p.) : ill., couv. ill. en coul. ; 21 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
https://scholarworks.bgsu.edu/acs_diss/90
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions